Pengaruh Beban Kerja, Stres Kerja, dan Work Family Conflict Terhadap Burnout Karyawan - Inggis Lineuwih, Intan; Sariwulan, Tuty; Fadillah Fidhayallah, Nadya (CV. Lafadz Jaya, 2023)
Along with the changes in the world of work that are affected by the existence of Covid-19, every company needs to minimize the risk that can arise from these changes. The presence of burnout syndrome can be a risk that threatens the quality of life of the company and the productivity of employee. The purpose of this study is to analyze burnout in employee affected by workload, work stress, and work family conflict. This research is classified as an associative type of research with quantitative research approaches. The research method used the census method (saturated sampling). The sample used was 60 respondents. The data collection process uses a questionnaire which is the analyze through multiple linear regression analysis techniques. Based on the data obstained, it can be concluded that workload (X1) has a positive but not significant effect on burnout (Y) in employee of PT. X. Work stress (X2) has a positive and significant effect on burnout (Y) in employee of PT. X. Work family conflict (X3) has a positive and significant effect on burnout (Y) in employee of PT. X. Simultaneously workload (X1), work stress (X2), and work family conflict (X3) has a positive and significant effect on burnout (Y) in employee of PT. X.